Colour Doppler evaluation of uterine and ovarian blood flow in patients of polycystic ovarian disease and post-treatment changes. Issue 10 (October 2020) - Dwivedi, A.N.D.; Ganesh, V.; Shukla, R.C.; Jain, M.; Kumar, I.
Abstract : AIM: To assess the morphology and colour Doppler parameters in patients with polycystic ovarian syndrome (PCOS) and also to assess the changes in Doppler parameters in follow-up patients, who underwent treatment. MATERIALS AND METHODS: The study was conducted on 50 women of reproductive age who had clinical and biochemical findings suggestive of PCOS. Clinico-hormonal parameters were recorded. Ultrasound and colour Doppler flow measurements of bilateral ovaries were performed in the early proliferative phase of the menstrual cycle. After assessment of the bilateral ovaries, colour Doppler ultrasound was used to evaluate the main uterine artery at the cervico-uterine junction. Follow-up imaging after 3 months was undertaken in patients who underwent treatment (metformin) and changes in the imaging and hormonal parameters were correlated. RESULTS: The mean value of luteinising hormone (LH) and the ratio of LH: follicle-stimulating hormone (FSH) was significantly higher in PCOS patients. Ultrasound parameters were significantly higher in PCOS patients. Ovarian stromal vessels in PCOS patients had a significantly higher peak systolic velocity (PSV), low resistance index (RI), and pulsatility index (PI). The PSV of uterine arteries were significantly decreased and the RI and PI were significantly increased. On follow-up patients revealed changes in hormonal parameters. CONCLUSION: PCOS is a heterogeneous disorder and is a convergence of multisystem endocrine derangements. Ultrasound is good diagnostic tool for PCOS and the use of Doppler aids in the evaluation of haemodynamic changes in small vessels of utero-ovarian circulation and in response assessment. Highlights: Patients were divided into polycystic ovarian disease and morphology. The patients showed predominantly peripheral and general cystic pattern. Imaging showed changes in ovarian and uterine arteries. Post treatment scan revealed positive changes in ultrasound and Doppler indices.